Patterned Duplex Fabric Based on Genetically Modified Spidroin for Smart Wound Management (Adv. Healthcare Mater. 4/2023). Issue 4 (6th February 2023) - Lin, Baoyang; Yuan, Liquan; Gao, Bingbing; He, Bingfang
Abstract : Wound Healing In article 2202213, Bingbing Gao, Bingfang He, and co‐workers fabricate a smart patterned DNA double helix (duplex)‐like fabric based on genetically modified spider silk protein (PDF‐S), which is inspired by soft plant tendrils, and is proposed for diabetic wound treatment.